DDDR-28. EGFR AND SRC-MEDIATED ACTIVATION OF STAT3 DRIVES RESISTANCE TO MITOTIC INHIBITORS IN GLIOBLASTOMA, AND CAN BE REVERSED WITH FDA-APPROVED DRUGS. (14th November 2022) - Kenchappa, Rajappa; Dovas, Athanassios; Argenziano, Michael; Meyer, Christian; Stopfer, Lauren; Banu, Matei; Pereira, Brianna; Griffith, Jessica; Mohammad, Afroz; Talele, Surabhi; Zarco, Natanael; Elmquist, William F; et al.
Abstract: While the allure of targeted therapies in oncology has been their high degree of specificity and potency for key tumor drivers, they have been disappointing in glioblastoma (GBM), even for drugs that are blood brain barrier permeable and CNS retained. This point is highlighted by the experience with mitotic spindle inhibitors, drugs which block the G2 M transition and induce mitotic catastrophe—a phenotype characterized by cell enlargement and polyploidy that leads to apoptotic cell death. We have shown that one of these, a potent inhibitor of the mitotic kinesin Kif11 (ispinesib), is highly active against GBM tumor initiating cells and prolongs survival in murine models of this disease. However, tumors eventually progress, reflecting the development of drug resistance. Although ispinesib resistant GBM cells develop mitotic catastrophe, they become highly resistant to the apoptosis that typically follows and continue to proliferate. We find that this apoptosis resistance requires phosphorylation of the transcription factor STAT3 at two residues—Y705 and S727. Phosphorylation of Y705, mediated by SRC kinase, translocates STAT3 to the nucleus where it induces transcription of anti-apoptotic proteins. Phosphorylation at S727, mediated by EGFR, translocates STAT3 to the mitochondria where it blocks release of cytochrome c—the penultimate effector in apoptosis. Simultaneously inhibiting both SRC and EGFR with FDA-approved, CNS permeant inhibitors reverses this resistance and significantly prolongs survival in ispinesib-treated GBM-bearing mice. Furthermore, we find that resistance to several other mitotic inhibitors also utilizes this STAT3-driven mechanism and can likewise be reversed with combined EGFR and SRC inhibition. Thus, our work demonstrates how a promising therapeutic approach, which has been disappointing in GBM, can in fact be rendered effective by anticipating and prospectively treating ab initio the mechanism that drives treatment resistance.